Antihyperuricemia Effectiveness of Ethanol Extract Combination of Bitter Melon (Momordica charantia) and Moringa (Moringa oleifera L.) in Caffeine-Induced Rats (Rattus norvegicus) - Mahmudah, Rifa’atul; Yusuf , Muhammad Ilyas; Risnawati, Risnawati (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Introduction: Hyperuricemia is a condition characterized by elevated blood uric acid levels exceeding normal limits. Herbal medicines, such as bitter melon (Momordica charantia) and moringa (Moringa oleifera), have potential efficacy in reducing uric acid levels. This study aims to evaluate the effectiveness of a combination of BME (Bitter Melon Extract) and MLE (Moringa Leaf Extract) as an anti-hyperuricemia treatment. Aims: This experimental study assesses the quality standardization of the extracts, including specific and non-specific parameters. The effectiveness of the combined extracts was tested on caffeine-induced hyperuricemic rats, which were divided into six groups: negative control (Na.CMC 0.5%), positive control (Allopurinol), and four treatment groups receiving different doses of BME and MLE (D1, D2, D3, D4). Result: The results showed that the combination of BME and MLE met the quality standard parameters. All four dosage variations demonstrated a reduction in uric acid levels. Among them, D3 (1.8 mg/kg BW of BME and 600 mg/kg BW of MLE) was the most effective, with a 41.3% reduction in uric acid levels. Statistical analysis using the Least Significant Difference (LSD) method indicated a significant difference between the negative control group and the treatment groups on the 7th day. Conclusion: The combination of BME and MLE has proven to be effective as an anti-hyperuricemia agent. Further research is needed to explore the potential of herbal medicines as alternative treatments for hyperuricemia.